Role of laboratory markers in identifying the severity of acute appendicitis in geriatric patients - Arıcı, Sinan; Adalı, Mert; Erol, Mehmet Fatih; Şen, Süleyman; Büyükavcı, Hüseyin; Tihan, Deniz (The European Research Journal, 2023)
Objectives: The main aim of our study is to investigate the effectiveness of laboratory markers in geriatric patients diagnosed with acute appendicitis in the emergency department. Methods: A total of 73 cases aged over 65 who underwent appendectomy were reviewed retrospectively. Age, sex, laboratory values of leukocyte count, neutrophil and lymphocyte values, platelets, serum sodium, aspartate aminotransferase (AST), alanine aminotransferase (ALT), C-reactive protein (CRP) and serum total bilirubin levels and pathological findings were investigated. The patients were divided into two different groups according to the pathology reports of appendicitis: complicated appendicitis (gangrenous/perforated appendicitis) (Group 1) and simple (uncomplicated) appendicitis (catarrhal or phlegmonous appendicitis) (Group 2). Results: A significant difference was found between Groups 1 and 2 concerning age, WBC, CRP, neutrophil, leukocyte, total bilirubin levels and neutrophil/lymphocyte ratio (NPR), and platelet/lymphocyte ratio.(PLR) No statistically significant differences were found for platelets, Na, AST and ALT levels. Conclusions: Elderly patients with complicated appendicitis often presented with higher WBC, CRP, total bilirubin, neutrophil, NLR and PLR levels, and lower lymphocyte levels. Moreover, these parameters are adjunctive data with a lower cost, easily available, and rapid markers which can be obtained in the emergency department.